Clinical and Radiographical Evaluation of Displaced Supracondylar Humerus Fractures in Children with Open Reduction and Internal Fixation from Lateral Approach at Dr. Soedirman Hospital in Kebumen - Dio Alif Zulfanda; Muhammad Abdul Azis (Universitas Malahayati Lampung, 2023)
ABSTRACT Supracondylar humerus fracture is the most common elbow fractur in children. This fracture requires proper diagnosis and treatment, otherwise it can cause functional impairment and complications. This study aims to assess outcome of displaced supracondylar humerus fracture in children by open reduction and pining from lateral approach. This research was descriptive quantitative using a retrospective method. All cases Gartland type III of supracondylar humerus fractures in children at Dr. Soedirman Hospital in Kebumen for 2015-2020, treated with open reduction and internal fixation from lateral approach. Outcomes were assessed according to the Flynn’s criteria and Mayo Elbow Performance Score. There were 59 patients, the age 3-15 years and the mean age 6.8 years. More cases were found in boys (59.3%) than girls (40.7%). The most common type of fracture was extension (98.3%). The side of fracture was more the left and was the non-dominant extremity (56%). No infection, vascular and nerve injuries. According to Flynn's criteria, cosmetic outcome in 55 of the 59 patients (93.2%) was excellent, in 4 patients (6.8%) good (P=0.051). Also, the functional outcome in 59 patiens (100%) were excellent. According to MEPS scoring, functional outcome in 58 patients (98.3%) was excellent and 1 patient (1.7%) had good. Overall, all cases were judged satisfactory (P=0.043). Treatment of supracondylar humerus fractures in children with open reduction and internal fixation from lateral approach is a safe with good clinical and radiographic results and can be applied. Keywords: Supracondylar Fractures, Open Reduction, Lateral Approach, Children.